(untitled) (Research, Society and Development, 2020)
Objective: evaluation of the forces resulting from the initial stretching of closed Nickel-titanium springs and the degradation of these forces after 28 days of stretching. Methodology: The sample comprised 80 Morelli Nickel-titanium closed coil springs, divided into 4 groups of 20 according to their length, 7, 9, 12 and 15mm. In each group, 10 spring coils suffered distension in 50 and 100% of its original length and were maintained in devices to simulate the distension. The resulting forces were measured with a tensiometer and compared with the force described by the manufacturer on the spring packaging (200 grams force). Measurements were performed in 2 time-points; right after the initial strain (T1) and after 28 days (T2), when the devices were kept in artificial saliva at a temperature of 37°C. For the statistical analysis, the Mann-Whitney test was applied to compare the forces in T1 with the manufacturer’s value and the paired t test to compare the forces between T1 and T2. In all statistical tests, a significance level of 5% was adopted. Result: In T1 the springs of 9, 12 and 15mm stretched by 50% showed significantly lower values ​​and the springs of 7 and 15mm stretched by 100% showed significantly higher values, both compared with the manufacturer’s recommendation. All groups of springs showed significant degradation of forces between T1 and T2, with percentage rates of force degradation from 7.1 to 21.9%. Conclusion: It is necessary to measure the forces of the springs during orthodontic treatment, aiming to establish an optimal force for tooth movement and thus optimizing the total treatment time.